Peran Dosen Pendidikan Agama Islam dalam Membangun Moderasi Beragama di Perguruan Tinggi - Asmarita, Asmarita (Pusat Riset dan Inovasi Nasional, 2025)
Religious moderation has become a strategic issue in the context of higher education in Indonesia as an effort to maintain social harmony and strengthen national character based on the values of tolerance, balance, and justice. This article aims to analyze the role of Islamic Education (PAI) lecturers in promoting religious moderation in universities. This study employs a descriptive qualitative approach through literature review and conceptual analysis of policies from the Ministry of Religious Affairs, the Islamic Education curriculum, and teaching practices in higher education environments. The findings indicate that PAI lecturers hold a strategic role as educators, role models, and agents of change in instilling the values of religious moderation among students. PAI lecturers are expected not only to deliver theological content but also to internalize the values of tolerance, respect for diversity, and the spirit of ukhuwah wathaniyah (national brotherhood) and ukhuwah insaniyah (human brotherhood). In conclusion, strengthening the capacity of PAI lecturers and integrating the values of moderation into the curriculum are strategic steps to build an inclusive and peaceful campus environment